Enacting acts of authentication in a robotics competition: An interpretivist study. Issue 3 (7th January 2015) - Verma, Geeta; Puvirajah, Anton; Webb, Horace
Abstract While the science classroom primarily remains a site for knowledge acquisition through teacher directed experiences, other sites exist outside of the classroom that allow for student generation of scientific knowledge. These sites provide opportunities for linguistic and social interactions to play a powerful role in situating students' science learning experiences. Augmenting students' formal school science experiences with informal experiences outside of the classroom enables them to intersect their personal knowledge with canonical disciplinary knowledge. This allows for conditions of practice that are more relevant to the students. In this study we introduce the notion of acts of authentication to examine the nature of students' linguistic and social activities in an informal setting—a regional robotics competition. These acts of authentication are a) participating in talk (including everyday); b) participating in productive disciplinary engagement (by co‐constructing and critiquing knowledge); and c) being a member of a community of practice. We used Critical Discourse Analysis to examine students' and mentor's dialogic language to gain insights into the nature of their robotics experiences. Our findings indicate that the robotics experience offered rich opportunities for students to engage in acts of authentication. Our study offers conceptual insights into how the culture of the robotics activities both constructs and is constructed by the linguistic and social experiences of the students and their mentors. © 2015 Wiley Periodicals, Inc. J Res Sci Teach 52: 268–295, 2015